1961
DOI: 10.1139/o61-131
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF NO2 AND SALTS OF NO2 UPON ESTABLISHED CELL LINES

Abstract: The effects of several concentrations of NO2, NaNO3, and NaNO2 respectively, upon strain L, mouse liver cells, and HeLa cells, were studied and a modified system designed to permit continuous exposure of cells to air pollutants is described. In NCTC medium 109 containing serum, cells tolerate concentrations of NO2 up to 4100 p.p.m. and some may even tolerate 8600 p.p.m. Removal of the serum lowers the lethal concentration of NO2 to less than 100 p.p.m. If the cells were covered only by a thin film of BSS (bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1968
1968
1982
1982

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Two hamster cell strains (embryo, tracheal) were planted at an initial density 1 X 105 cells per filter in 35-mm culture dishes, and samples were fixed, stained, and mounted on days 3 and 5 after planting. Good morphology was judged as a flat, even appearing cytoplasm as opposed to a rounded or spindly appearance (3)(4)(5)(6) cytoplasmic extensions from the main cell body extending at times into the pores of the filters). Cells on filters with pore sizes of 3.0 pm or greater developed a spindly appearance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two hamster cell strains (embryo, tracheal) were planted at an initial density 1 X 105 cells per filter in 35-mm culture dishes, and samples were fixed, stained, and mounted on days 3 and 5 after planting. Good morphology was judged as a flat, even appearing cytoplasm as opposed to a rounded or spindly appearance (3)(4)(5)(6) cytoplasmic extensions from the main cell body extending at times into the pores of the filters). Cells on filters with pore sizes of 3.0 pm or greater developed a spindly appearance.…”
Section: Resultsmentioning
confidence: 99%
“…Angeles County have been reported (1)(2)(3)(4). However, for precise estimation of these effects, one must duly account for the seasonal behavior and the random fluctuations in the pollutant concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Saltzman has reported that for every mole of NO 2 dissolved, 0.72 moles of NO 2 ions are produced, as indicated by specific interaction with the azo radical of the Saltzman reagent. Pace & Associates, 1 have demonstrated that NaN0 2 , but not NaN0 3 , produced a death rate of cells in tissue culture which was comparable to the effect resulting from a direct exposure of the cells to NO2 gas. To facilitate the introduction of NO 2 to the cells, NaN0 2 was used as a starting material rather than NO 2 gas.…”
Section: Functional and Morphological Response Of In Vitro Lung And Mmentioning
confidence: 94%